2020
DOI: 10.1073/pnas.2003667117
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor-enabled functional expression of fruit fly, honeybee, and bumblebee nicotinic receptors reveals picomolar neonicotinoid actions

Abstract: The difficulty of achieving robust functional expression of insect nicotinic acetylcholine receptors (nAChRs) has hampered our understanding of these important molecular targets of globally deployed neonicotinoid insecticides at a time when concerns have grown regarding the toxicity of this chemotype to insect pollinators. We show that thioredoxin-related transmembrane protein 3 (TMX3) is essential to enable robust expression in Xenopus laevis oocytes of honeybee ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 50 publications
(70 reference statements)
5
108
2
Order By: Relevance
“…Among these, we focused on nAChRα1 , nAChRα2, nAChRα3, nAChRβ1 and nAChRβ2 because the knock-down of these genes in dsx + Tdc2 + ( tub >GAL80>, dsx-FLP; Tdc2-GAL4 ) or Tdc2 neurons ( Tdc2-GAL4 ) increased the GSC number in virgin females similar to ppk >ChAT RNAi ( Figure 6D and Figure 6—figure supplement 1A ). We then confirmed the expression of these acetylcholine receptor genes in Tdc2 neurons by generating a knock-in T2A-GAL4 line as previously described ( Kondo et al, 2020 ; Ihara et al, 2020 ) for each 5 nAChR subunit s and observed their expression with UAS-mCD8::GFP . All of the five knock-in-GAL4 expressions were detected in anti-Tdc2 positive neurons around the ovary, suggesting that the ovary-projecting dsx + Tdc2 + neurons expresses these nAChRs ( Figure 6—figure supplement 1B–F ).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Among these, we focused on nAChRα1 , nAChRα2, nAChRα3, nAChRβ1 and nAChRβ2 because the knock-down of these genes in dsx + Tdc2 + ( tub >GAL80>, dsx-FLP; Tdc2-GAL4 ) or Tdc2 neurons ( Tdc2-GAL4 ) increased the GSC number in virgin females similar to ppk >ChAT RNAi ( Figure 6D and Figure 6—figure supplement 1A ). We then confirmed the expression of these acetylcholine receptor genes in Tdc2 neurons by generating a knock-in T2A-GAL4 line as previously described ( Kondo et al, 2020 ; Ihara et al, 2020 ) for each 5 nAChR subunit s and observed their expression with UAS-mCD8::GFP . All of the five knock-in-GAL4 expressions were detected in anti-Tdc2 positive neurons around the ovary, suggesting that the ovary-projecting dsx + Tdc2 + neurons expresses these nAChRs ( Figure 6—figure supplement 1B–F ).…”
Section: Resultsmentioning
confidence: 62%
“…The following GAL4 and LexA strains were used: c587-GAL4 ( Manseau et al, 1997 ) (gift from Hiroko Sano, Kurume University, Japan), R44E10-GAL4 ( Deady and Sun, 2015 ) (a gift from Jianjun Sun, University of Connecticut, USA) , RS-GAL4 ( Lee et al, 2009 ) (a gift from Kyung-An Han, Pennsylvania State University, USA), nSyb-GAL4 (BDSC #51941), nSyb-GAL80 ( Harris et al, 2015 ) (a gift from James W. Truman, Janelia Research Campus, USA), tj-GAL4 (DGRC #104055), R13C06-GAL4 (BDSC #47860), 109–30 GAL4 (BDSC #7023), c355-GAL4 (BDSC #3750), c306-GAL4 (BDSC #3743), slbo-GAL4 (BDSC #6458), bab1-GAL4 ( Bolívar et al, 2006 ) (a gift from Satoru Kobayashi, University of Tsukuba, Japan), nos-GAL4 (DGRC #107748), tub >FRT >GAL80>FRT (BDSC #38879), Oamb KI-RD -GAL4 (BDSC#84677) ( Deng et al, 2019 ) , Oamb-KI-T2A-GAL4, nAChRα1-T2A-GAL4, nAChRα2-T2A-GAL4, nAChRα3-T2A-GAL4, nAChRβ1-T2A-GAL4, nAChRβ2-T2A-GAL4 ( Kondo et al, 2020 ; Ihara et al, 2020 ), ChaT-GAL4 (BDSC #6793), ppk-GAL4 ( Grueber et al, 2007 ) (a gift from Hiroko Sano, Kurume University, Japan), and SPSNs-LexA ( Feng et al, 2014 ) (a gift from Young-Joon Kim, Gwangju Institute of Science and Technology, South Korea).…”
Section: Methodsmentioning
confidence: 99%
“…For example, honey bees (Apis mellifera) are particularly sensitive to imidacloprid (66), which is known to cause oxidative stress in this species (14). Imidacloprid has been shown to target orthologous nAChR subunits in A. mellifera and D. melanogaster, but the A. mellifera receptors respond to an insecticide concentration an order of magnitude lower than the receptors of D. melanogaster (21). Further, A. mellifera has a reduced capacity to metabolize imidacloprid (66).…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila loss-of-function mutants for these genes are only moderately resistant (17), indicating that imidacloprid may target nAChR subtypes that contain additional subunits. Recent heterologous expression studies indicate that the α1, α2, β1, and β2 subunits contribute to nAChRs targeted by imidacloprid (21). The molecular and cellular events downstream of imidacloprid binding to an nAChR have not been described.…”
Section: Significancementioning
confidence: 99%
“…While our study may help understand the mechanism through which insects tolerate anthrax, resulting in their greater opportunity to transmit the anthrax-causing bacteria, it further suggests that PA 20 could be used beneficially in agriculture. Since fruit flies and mosquitoes are known to act as plant pollinators [ 71 , 72 ], PA 20 should be further evaluated for its ability to reduce the sensitivity of pollinating insects to bacterial pathogens, such as Serratia and Bacillus species [ 73 75 ].…”
Section: Discussionmentioning
confidence: 99%